The origin of the Loncopué Trough in the retroarc of the Southern Central Andes from field, geophysical and geochemical data - Rojas Vera, Emilio Agustin (2014)
This work analyzes through field, geophysical, geochemical and geochronological data, a particular setting of the Southern Andes in which an extensional system is flanking the mountain front. This setting is represented by the Loncopué Trough, whose origin is discussed for this part of the Andes. This work reconstructs 3-dimensionally the structure of this basin and its evolution through time, since Jurassic times as a series of isolated depocenters, to Late Cretaceous-Eocene times with the construction of a positive relief that subsequently was relaxed through two extensional stages during the late Oligocene-early Miocene and the Pliocene-Quaternary respectively. The last episode of extension is characterized by an initial stage with a series of caldera-collapses in the latest Pliocene-early Quaternary. This passed to a stage of development of a broad basaltic plateau in pre- and inter-glacial times, circumscribed with new radiometric data to the Pleistocene. Quaternary products in northern and central Loncopué Trough have chemical relations that are intermediate between the arc front and the southern Loncopué Trough volcanic rocks studied in previous works. Thus, retroarc eruptions would be part of an extended arc configuration that goes from typical arc series in the northern part of the trough to within-plate series in the south. Low elastic thicknesses computed from gravity data in this work correlate with the area of retroarc volcanic activity. Magnetic data have allowed determining the Curie isotherm, showing two areas of relatively abnormal heat flow, one along the Loncopué Trough itself and the other in the foreland zone. This scenario is discussed through three main hypotheses: an occurrence linked to a slab-steepening after a shallow subduction in the area; co-seismic crustal stretching linked to giant earthquakes in the subduction zone; and, finally slab-tearing associated with asthenospheric upwelling.